2019
DOI: 10.1007/s11002-019-09496-6
|View full text |Cite
|
Sign up to set email alerts
|

When more likes is not better: the consequences of high and low likes-to-followers ratios for perceived account credibility and social media marketing effectiveness

Abstract: When more likes is not better: the consequences of high and low likes-tofollowers ratios for perceived account credibility and social media marketing effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 10 publications
(11 reference statements)
2
24
0
2
Order By: Relevance
“…This study also furthers the bandwagon literature in the realm of social media advertising by showing that the bandwagon cues that accompany social media ads can influence consumer psychology and ad effectiveness. In line with previous research that demonstrated that Instagram users formed their credibility judgment of social media accounts based on the number of likes a post receives (De Vries, 2019) and the number of followers of the influencer (Weismueller et al, 2020), this study demonstrated similar pattern for Twitter: audience metrics including the number of likes, the number of retweets and the number of comments collectively influenced Twitter users' evaluation of social media ads and their emotional reactions to ads, which in turn affected their behavioral intention related to the product and the brand. In addition, this study extends the existing literature by uncovering the underlying cognitive and emotional mechanisms through which bandwagon cues can improve ad persuasion on social media.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study also furthers the bandwagon literature in the realm of social media advertising by showing that the bandwagon cues that accompany social media ads can influence consumer psychology and ad effectiveness. In line with previous research that demonstrated that Instagram users formed their credibility judgment of social media accounts based on the number of likes a post receives (De Vries, 2019) and the number of followers of the influencer (Weismueller et al, 2020), this study demonstrated similar pattern for Twitter: audience metrics including the number of likes, the number of retweets and the number of comments collectively influenced Twitter users' evaluation of social media ads and their emotional reactions to ads, which in turn affected their behavioral intention related to the product and the brand. In addition, this study extends the existing literature by uncovering the underlying cognitive and emotional mechanisms through which bandwagon cues can improve ad persuasion on social media.…”
Section: Discussionsupporting
confidence: 89%
“…There is evidence that consumer evaluation of source credibility can influence how they respond to the social media account and the persuasive branded messages that they encounter on social media (e.g. De Vries, 2019;Jin and Muqaddam, 2019;McLaughlin, 2016 et al (2018) found that brand credibility positively affected brand image and social media users' purchase intention of the brand. In addition, a line of research focusing on influencer marketing has collectively discovered that social media users' perceived credibility judgment of the influencers could affect their trust in influencers' branded content (Lou and Yuan, 2019), their brand attitude (Jin and Muquaddam, 2019) and purchase intention (Lou and Yuan, 2019;M€ uller et al, 2018;Sokolova and Kefi, 2020;Weismueller et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This current study implemented additional feature engineering from the data provided in Section 2.2.2 above to more holistically capture user activity on Instagram. The four features created include: follow ratio ( ) ( Longobardi et al, 2020 ; Woodruff et al, 2018 ) engagement ( ) sum of average comments and average likes per follower ( ) ( De Vries, 2019 ) average comments-to-average-likes ratio ( ) …”
Section: Methodsmentioning
confidence: 99%
“…With an average of 7.3 likes per post, interaction was relatively low [ 13 , 14 ]. The highest numbers of interactions were achieved for posts in the categories of engagement and self-awareness.…”
Section: Discussionmentioning
confidence: 99%